2019
DOI: 10.1002/mma.5462
|View full text |Cite
|
Sign up to set email alerts
|

Boundedness and compactness characterizations of Cauchy integral commutators on Morrey spaces

Abstract: Let CΓ be the Cauchy integral operator on a Lipschitz curve Γ. In this article, the authors show that the commutator [b,CΓ] is bounded (resp, compact) on the Morrey space Lp,λfalse(double-struckRfalse) for any (or some) p  ∈  (1,∞) and λ  ∈  (0,1) if and only if b∈0.1emBMOfalse(double-struckRfalse) (resp, CMOfalse(double-struckRfalse)). As an application, a factorization of the classical Hardy space H1false(double-struckRfalse) in terms of CΓ and its adjoint operator is obtained.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 39 publications
(90 reference statements)
0
24
0
Order By: Relevance
“…In this section, we first obtain a simple but useful auxiliary lemma (see Lemma 2.1 below), which is on the domination of |b(z) − α Q (b)| for a given real-valued function b ∈ L 1 loc (C) by the difference |b(z) − b(u)| pointwise on subsets of Q × Q, where Q and Q are squares and α Q (b) is the median value of b over Q . Compared to [22,27], our method adopted in the proof of Theorem 1.3 avoids the use of the so-called local mean oscillation. Section 3 is devoted to the proof of Theorem 1.4 and is divided into two subsections.…”
Section: Introduction and Statement Of Main Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this section, we first obtain a simple but useful auxiliary lemma (see Lemma 2.1 below), which is on the domination of |b(z) − α Q (b)| for a given real-valued function b ∈ L 1 loc (C) by the difference |b(z) − b(u)| pointwise on subsets of Q × Q, where Q and Q are squares and α Q (b) is the median value of b over Q . Compared to [22,27], our method adopted in the proof of Theorem 1.3 avoids the use of the so-called local mean oscillation. Section 3 is devoted to the proof of Theorem 1.4 and is divided into two subsections.…”
Section: Introduction and Statement Of Main Resultsmentioning
confidence: 99%
“…Thus, in the proof of Theorem 1.4(i), we use some ideas from [21,7] Subsection 3.2 is devoted to the proof of Theorem 1.4(ii). As in the unweighted case (see, for example, [28,27]), we first obtain a lemma for the upper and the lower bounds of integrals of [b, B] f j related to certain squares Q j , for any real-valued function b ∈ BMO(C) and proper functions f j defined by Q j with j ∈ N; see Lemma 3.5 below. Since a general A p (C) weight is not invariant under translations, besides Lemma 3.5, we also obtain a variant of Lemma 3.5, where the geometrical relation of {Q j } j∈N are involved; see Lemma 3.6 below.…”
Section: Introduction and Statement Of Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Uchiyama [25] then showed that [b, R j ] is compact on L p (R n ) with 1 < p < ∞ if and only if b ∈ VMO(R n ), the space of functions with vanishing mean oscillation on R n . Later on and recently, there has been an intensive study of the compactness of commutators of singular integrals in many different settings, such as the Riesz transform associated with Bessel operator on the positive real line, the Cauchy's integrals on the real line, the Calderón-Zygmund operator associated with homogeneous kernels Ω(x) |x| n on R n , and the multilinear Riesz transforms, see for example [4,9,13,17,18,19,23] and related references therein.…”
Section: Introduction and Statement Of Main Resultsmentioning
confidence: 99%